BRCA1-like profile is not significantly associated with survival benefit of non-myeloablative intensified chemotherapy in the GAIN randomized controlled trial - Rossum, Annelot van; Marmé, Frederik (Breast cancer research and treatment, 2017)
PurposeThe BRCA1-like profile identifies tumors with a defect in homologous recombination due to inactivation of BRCA1. This profile has been shown to predict which stage III breast cancer patients benefit from myeloablative, DNA double-strand-break-inducing chemotherapy. We tested the predictive potential of the BRCA1-like profile for adjuvant non-myeloablative, intensified dose-dense chemotherapy in the GAIN trial.MethodsLymph node positive breast cancer patients were randomized to 3 × 3 dose-dense cycles of intensified epirubicin, paclitaxel, and cyclophosphamide (ETC) or 4 cycles concurrent epirubicin and cyclophosphamide followed by 10 cycles of weekly paclitaxel combined with 4 cycles capecitabine (EC-TX). Only triple negative breast cancer patients (TNBC) for whom tissue was available were included in these planned analyses. BRCA1-like or non-BRCA1-like copy number profiles were derived from low coverage sequencing data.Results119 out of 163 TNBC patients (73%) had a BRCA1-like profile. After median follow-up of 83 months, disease free survival (DFS) was not significantly different between BRCA1-like and non-BRCA1-like patients [adjusted hazard ratio (adj.HR) 1.02; 95% confidence interval (CI) 0.55-1.86], neither was overall survival (OS; adj.HR 1.26; 95% CI 0.58-2.71). When split by BRCA1-like status, DFS and OS were not significantly different between treatments. However, EC-TX seemed to result in a trend to an improvement in DFS in patients with a BRCA1-like tumor, while the reverse accounted for ETC treatment in patients with a non-BRCA1-like tumor (p for interaction = 0.094).ConclusionsThe BRCA1-like profile is not associated with survival benefit for a non-myeloablative, intensified regimen in this study population. Considering the limited cohort size, capecitabine might have additional benefit for TNBC patients.